High-throughput optical imaging technology for large-scale single-cell analysis of live Euglena gracilis - Lei, Cheng; Nakagawa, Yuta; Nagasaka, Yuzuki; Ding, Tianben; Kanno, Hiroshi; Toyokawa, Chihana; Niizuma, Kuniyasu; Suzuki, Kengo; Li, Ming; Sunna, Anwar; Hampl, Vladimir; Goda, Keisuke (TrAC, Trends in analytical chemistry (Regular ed.), 2024)
Euglena gracilis, a flagellated, single-celled organism shaped like a spindle, belongs to the Euglenozoa phylum. This protist is predominantly found in freshwater bodies such as lakes and ponds. Unique in its ability to perform photosynthesis and heterotrophic feeding, E. gracilis can produce organic materials on its own or absorb them from the environment. This intriguing blend of plant and animal traits, coupled with promising biotechnological applications, have made it a subject of extensive research. Notably, E. gracilis has been used for biofuel production and synthesis of various compounds such as amino acids and vitamins. For these applications, rapid assessment of single E. gracilis cells within populations is essential. This paper introduces recent advancements in high-throughput optical imaging technology that enables large-scale, single-cell analysis of E. gracilis. We review the benefits and limitations of various methods within this technology, along with discussing its future potential. •Euglena gracilis is a promising species for biomedical and environmental applications.•Large-scale single-cell analysis of E. gracilis is critical for the applications.•Several high-throughput optical imaging methods for this goal are introduced.•Key applications enabled by the methods are discussed.